Proceso de ASC - FRAUDE ACADEMICO EN ESTUDIANTES UNIVERSITARIOS. UN ESTUDIO DE CASO EN UNA INSTITUCION DE EDUCACION SUPERIOR EN MEDELLIN (2020)
In the Antioquia Legal program (2012-2015), the perception of academic dishonesty was highlighted as a major concern in higher education institutions in the region, leading to various campaigns in support of a "University without Cheating." In Medellín, one of the most recurring and influential actions related to this type of dishonesty was academic fraud. Therefore, the objective of the research group is to estimate the factors that contribute to fraud.